Muscle and Systemic Molecular Responses to a Single Flywheel Based Iso-Inertial Training Session in Resistance-Trained Men - Annibalini, Giosuè; Contarelli, Serena; Lucertini, Francesco; Guescini, Michele; Maggio, Serena; Ceccaroli, Paola; Gervasi, Marco; Ferri Marini, Carlo; Fardetti, Francesco; Grassi, Eugenio; Stocchi, Vilberto; Barbieri, Elena; et al. (Frontiers in Physiology, 2019)
Growing evidence points to the effectiveness of flywheel (FW) based iso-inertial resistance training in improving physical performance capacities. However, molecular adaptations induced by FW exercises are largely unknown. Eight resistance-trained men performed 5 sets of 10 maximal squats on a FW device. Muscle biopsies (fine needle aspiration technique) and blood samples were collected before (t0), and 2h (t1) after FW exercise. Blood samples were additionally drawn after 24h (t2) and 48h (t3). Paired samples t-tests revealed significant increases, at t1, of mRNA expression of the genes involved in inflammation, in both muscle (MCP-1, TNF-α, IL-6) and peripheral blood mononuclear cells (IkB-α, MCP-1). Circulating extracellular vesicles (EVs) and EV-encapsulated miRNA levels (miR-206, miR-146a) significantly increased at t1 as well. Conversely, muscle mRNA level of genes associated with muscle growth/remodeling (IGF-1Ea, cyclin D1, myogenin) decreased at t1. One-way repeated measure ANOVAs, with Bonferroni corrected post-hoc pairwise comparisons, revealed significant increases in plasma concentrations of IL-6 (t1; t2; t3) and muscle creatine kinase (t1; t2), while IGF-1 significantly increased at t2 only. Our findings show that, even in experienced resistance trained individuals, a single FW training session modifies local and systemic markers involved in late structural remodeling and functional adaptation of skeletal muscle.